A retrospective clinical study on the survival of posterior composite restorations in a primary care dental outreach setting over 11years. (March 2021) - Wong, Constance; Blum, Igor R.; Louca, Chris; Sparrius, Martin; Wanyonyi, Kristina
Abstract: Objectives: To investigate the survival in terms of time to re-intervention of composite restorations in posterior teeth among patients attending for treatment at a primary care dental outreach setting over an 11-year period and to determine whether dental, patient or operator factors influenced this. Methods: Electronic primary dental care data were collected on individual patients, including information on their dental treatment and socio-demographics as well as service provision, key performance indicators and student activity. Results: A total of 1086 patients had at least one posterior composite placed between 2007 and 2018. This amounted to 3194 restorations placed of which 308 had a re-intervention within the 11-year period. For all restorations, the annual failure rate at 1 year was 5.73 %, at 5 years was 16.78 % and at 10 years was 18.74 %. A logistic regression showed that when compared to the least deprived 5 th quintile, the most deprived 1 st and 2 nd quintiles were significantly less likely to have a re-intervention, being 49.2 % (p = 0.022) and 53.2 % (p = 0.031) less likely, respectively. Conclusions: The survival rates of posterior composite restorations placed at a single outreach centre providing undergraduate dental training in the South of England, mirrors other studies. The new findings presented suggest similar re-intervention rates between dental students and dental hygiene-therapy students. This study's findings around patient deprivation and rate and time of re-intervention raises important questions related to the need for targeted dental and after care for certain groups in the population. Clinical significance: Understanding the factors associated with re-intervention of restorations provided to patients has an impact on patients and dental practices. Also, as we consider widening use of skill mix in dentistry to increase access to care, parity in provision of treatments within the dental team increases opportunities for delegation of tasks.